The contribution of pain and disability on the transition from acute to chronic pain-related TMD: A 3-month prospective cohort study - Velly, Ana Miriam; Elsaraj, Sherif M.; Botros, Jack; Samim, Firoozeh; der Khatchadourian, Zovinar; Gornitsky, Mervyn (Frontiers in Pain Research, 2022)
Although most cases of pain-related temporomandibular disorders (TMD) are mild and self-limiting, about 10% of TMD patients develop severe disorders associated with chronic pain and disability. It has been suggested that pain intensity contributes to the transition from acute to chronic pain-related TMD. Therefore, the aims of this current prospective cohort study were to assess if pain intensity, pain always being present, pain or stiffness on awakening, jaw activities, and interference, were associated with the transition from acute to chronic pain-related TMD at 3 months of follow-up. One hundred and nine participants, recruited from four clinics in Montreal and Ottawa, received examinations and completed the required instruments at baseline and at the 3rd month of follow-up. In a multivariable analysis including sex, age, characteristic pain index (CPI) (OR = 1.03, 95%CI = 1.01–1.06, P = 0.005), moderate to severe average pain intensity (OR = 3.51, 95%CI = 1.24–9.93, P = 0.02), disability points score (OR = 1.29, 95%CI = 1.06–1.57, P = 0.01), interferences (ORs = 1.30–1.32, P = 0.003–0.005), screening score (OR = 1.37, 95%CI = 1.08–1.76, P = 0.01), and pain always present (OR = 2.55, 95%CI = 1.08–6.00, P = 0.03) assessed at first-visit were related to the transition outcome at the 3rd month of follow-up. Further, we found that if 4 patients with acute pain-related TMD on average were exposed to these risk factors at baseline, 1 would have the transition from acute to chronic pain at 3 months of follow-up. Results indicate that these factors are associated with the transition from acute to chronic pain-related TMD, and therefore should be considered as important factors when evaluating and developing treatment plans for patients with pain-related TMD.